In vitro antiprotozoal activity of crude extract and leaf partitions of Diplopterys Pubipetala (Malpighiaceae) - Sacramento, Veronica de Melo; Resende, Daniela de Melo; Cerávolo, Isabela Penna; Murta, Silvane Maria Fonseca; Alves, Tânia Maria de Almeida; Royo, Vanessa de Andrade (Disciplinarum Scientia | Saúde, 2025)
The in vitro antiprotozoal activity of the hydroethanolic extract and its partitions (hexane, dichloromethane, ethyl acetate, and methanol) from Diplopterys pubipetala (Malpighiaceae) leaves was evaluated against the protozoa Trypanosoma cruzi, Leishmania amazonensis, and Plasmodium falciparum. The samples were obtained from the collection of young, healthy leaves and subjected to the preparation of the hydroethanolic extract and subsequent partitioning, following previously established methodologies. In the biological assays, all samples showed less than 30% inhibition of protozoan activity, failing to meet the minimum criteria for the characterization of relevant biological activity. These results are consistent with the literature, which also reports low antiprotozoal activity in Malpighiaceae species, although some have demonstrated phytotherapeutic potentials related to antioxidant and anti-inflammatory activities in recent studies. It is concluded that further studies are required to investigate natural compounds as promising alternatives in the development of treatments for neglected diseases caused by protozoa.